Total Oesophagogastric Dissociation in Neurologically Impaired Children: 18 Years' Experience and Long-term Follow-up. Issue 4 (April 2020) - Battaglia, Sonia; Orizio, Paolo; Boroni, Giovanni; Cheli, Maurizio; Colusso, Mara Marcella; Parolini, Filippo; Bianchi, Adrian; Alberti, Daniele
ABSTRACT: Objectives: Total oesophagogastric dissociation (TOGD) is an alternative antireflux surgery for neurologically impaired children because of a 16% to 38% fundoplication failure rate. This study evaluates TOGD's feasibility and its long-term efficacy both as a Primary and as a "Rescue" procedure after failed fundoplication. Methods: Thirty patients (18 boys) who underwent TOGD between 2000 and 2018 in 2 Italian Centres were retrospectively reviewed. Twenty-three were Primary procedures and 7 were "Rescue" ones. Inclusion criteria were severe neurodisability, intractable gastroesophageal reflux, and dysphagia. Results: Preoperatively, all children had regurgitation, vomiting or retching, and 93% had unsafe swallowing and aspiration, with recurrent chest infections/aspiration pneumonia. Median relative weight was 77% (48%--118%). All patients were taking antireflux medication before surgery. Median age at TOGD was 6.48 years (0.69--22.18). Median follow-up was 3.5 years (0.6–17.7). No recurrence of gastroesophageal reflux (GER) and vomiting was recorded. The number of chest infections and length of hospital stay showed a significative decrease ( P value <0.0001 for both), whereas median relative weight reached 101% ( P value 0.002). Parents'/caregivers' perception of outcome showed a significative improvement. Six patients (20%) experienced early complications and 3 required surgical intervention. Three late complications (10%) also required surgery. There was no surgery-related mortality. Conclusion: TOGD is an effective procedure with an acceptably low complication rate for children with severe neurological impairment and is followed by a major improvement in general health and quality of life for children and families. There was no substantial difference in outcome between Primary and "Rescue" procedures.